Phenotypic Selection of Magnetospirillum magneticum (AMB‐1) Overproducers Using Magnetic Ratcheting. (5th September 2017) - Tay, Andy; Murray, Coleman; Di Carlo, Dino
Abstract: Magnetosomes, magnetic nanoparticles (MNPs) encapsulated in lipid membranes produced by magnetotactic bacteria (MTB), have superior properties such as a narrow size distribution, making them of potential significant value for biomedical and industrial applications. However, the slow growth rate and genetic complexity of MTB have thus far limited large scale production of biologically synthesized MNPs. This problem is compounded by a lack of a platform to select MTB of interest. Here, the development of a magnetic ratcheting system that facilitates automated, live, and quantitative isolation of Magnetospirillum magneticum (AMB‐1) based on their phenotype, i.e., number of MNPs is described. Using repeated (five) cycles of random chemical mutagenesis and magnetic selection, AMB‐1 overproducers that biomineralize on average 2.2‐fold more MNPs (≈25) than the widely available strain AMB‐1 are generated. The size, shape, and magnetic properties of the MNPs of the overproducers are also similar to the control AMB‐1, supporting the utility of the platform for enriching MTB with overproducer phenotypes. Abstract : Magnetosomes, magnetic nanoparticles (MNPs) encapsulated in lipid membranes produced by magnetotactic bacteria, have superior properties such as a narrow size distribution, making them of potential significant value for biomedical and industrial applications. Here, the development of a magnetic ratcheting system that facilitates automated, live, and quantitative isolation of Magnetospirillum magneticum (AMB‐1) based on their phenotype, i.e., number of MNPs, is described.